Understanding the Role of Social Media in Modern Marketing Communications - Sanan Waheed Khan; Hui Geng; Vahid Norouzi Larsari; Zohaib Hassan Sain (International Journal of Marketing and Digital Creative, 2023)
This study’s objective is to investigate the efficacy of brand communication activities carried out by large Malaysian companies on the social media platforms Facebook, Twitter, and Instagram by analyzing the message appeals, orientation and customer reactions. The instructive message content received fewer responses than the interactive brand postings. Instagram was better suited for interactive material that combined informative and entertaining appeals, while Twitter was more successful for informational appeals. Facebook, on the other hand, functioned better for interactive postings related to amusement. On Facebook and Instagram, the post with the most replies was an interactive brand post that appealed to a variety of people, while the one with the fewest responses was a message that focused on the authors’ interests and had an instructive appeal. The findings contribute to an expansion of the marketing literature regarding the use of new media for marketing communication and advise marketing practitioners to consider and employ a variety of inventive brand communication strategies in order to boost the effectiveness of social media marketing when using multiple platforms. This is one of the first research that compares the efficiency of creative messaging strategy on numerous social media platforms. Additionally, it presents insightful insights into social media marketing practices in Malaysia.